Global inequalities in the double burden of malnutrition and associations with globalisation: a multilevel analysis of Demographic and Health Surveys from 55 low-income and middle-income countries, 1992–2018. Issue 4 (April 2022) - Seferidi, Paraskevi; Hone, Thomas; Duran, Ana Clara; Bernabe-Ortiz, Antonio; Millett, Christopher
Summary: Background: Low-income and middle-income countries (LMICs) face a double burden of malnutrition (DBM), whereby overnutrition and undernutrition coexist within the same individual, household, or population. This analysis investigates global inequalities in household-level DBM, expressed as a stunted child with an overweight mother, and its association with economic, social, and political globalisation across country income and household wealth. Methods: We pooled anthropometric and demographic data for 1 132 069 children (aged <5 years) and their mothers (aged 15–49 years) from 189 Demographic and Health Surveys in 55 LMICs between 1992 and 2018. These data were combined with country-level data on economic, social, and political globalisation from the Konjunkturforschungsstelle Globalisation Index and gross national income (GNI) from the World Bank. Multivariate associations between DBM and household wealth, GNI, and globalisation and their interactions were tested using multilevel logistic regression models with country and year fixed-effects and robust standard errors clustered by country. Findings: The probability of DBM was higher among richer households in poorer LMICs and poorer households in richer LMICs. Economic globalisation was associated with higher odds of DBM among the poorest households (odds ratio 1·49, 95% CI 1·20–1·86) compared with the richest households. These associations attenuated as GNI increased. Social globalisation was associated with higher odds of DBM (1·39, 95% CI 1·16–1·65), independently of household wealth or country income. No associations were identified between political globalisation and DBM. Interpretation: Increases in economic and social globalisation were associated with higher DBM, although the impacts of economic globalisation were mostly realised by the world's poorest. The economic patterning of DBM observed in this study calls for subpopulation-specific double-duty actions, which should further aim to mitigate the potential negative and unequal impacts of globalisation. Funding: UK Biotechnology and Biological Sciences Research Council. Translations: For the Spanish and Portuguese translations of the abstract see Supplementary Materials section.